Hubungan Pelayanan Resep Obat dengan Kepuasan Pasien di Puskesmas Kecamatan Pasar Rebo Jakarta Timur Tahun 2015 - Juliani Juliani; Herlina Herlina (STIKes Persada Husada Indonesia, 2016)
Shifting the public and consumers is a result of increased knowledge and consumer awareness of health improvement. People who are aware of their right to health care and medicine, ethical and legal issues are increasing as people receive health services. Provision of health services that are less satisfying and less human or not as expected, the legal problems and ethical dilemmas will increase. The aim of research is to determine the relationship between prescription services and patient satisfaction in Puskesmas Kecamatan Pasar Rebo, East Jakarta. Type analytic survey research using cross sectional design. The study was conducted from March to May 2015 with a population of 9504 inhabitants and the sample of 100 respondents was searched using random sampling techniques. Chi-square statistic test found that there is no relationship between variable Reliability, Responsiveness, Assurance, Empathy and Tangible with the level of patient satisfaction. Respondent’s level of satisfaction in the service of prescription drugs say satisfied more than that to says less satisfied. The clerk at the service of prescription drugs while improving the quality of service so that visitors will still be satisfied.